2020
DOI: 10.9734/jpri/2020/v32i830475
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of Thermally Treated Rice Husk for Removal of Sulfamethazine Antibiotic from Pharmaceutical Wastewater

Abstract: Equilibrium sorption of the Thermally Treated Rice Husk (TTRH) for Sulfamethazine (SMT) adsorption was studied. The Physico-chemical properties of the modified rice husk were determined. The equilibrium sorption data were fitted into Langmuir, Freundlich and Dubinin–Radushkevich isotherms. Of the three adsorption isotherm, the R2 value of Langmuir isotherm model was the highest. Also compared to other isotherms the AARE coefficient for the Langmuir isotherm is low, which indicates favorable sorption. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Studies from Bello et al . on scavenging of MG onto Citrus grandis peels further supported these findings 38 , 56 .…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Studies from Bello et al . on scavenging of MG onto Citrus grandis peels further supported these findings 38 , 56 .…”
Section: Resultssupporting
confidence: 64%
“…The R 2 > 0.98 is an indication of a better description of equilibrium data by The DKR mean energy (E) value being less than 8 kJ indicated that the mechanism is physisorption. Studies from Bello et al on scavenging of MG onto Citrus grandis peels further supported these findings 38,56 .…”
Section: Resultsmentioning
confidence: 79%
“…Adsorption is a surface protocol that contracts mainly with the use of surface forces. Moreover, when a solution consisting absorbable solute (adsorbate) approaches into contact with a compact-solid (adsorbent), with extremely porous surface assembly intermolecular forces (liquid-solid) of attraction projects the solute to be concerted at the surface of solid [5].…”
Section: Adsorption Methods (Ams)mentioning
confidence: 99%
“…Adsorption is utilized as the uppermost class treatment technique for the elimination of mixed organic contaminants, for instance antibiotics from PWW [5]. The major characteristics of the adsorbents are robust affinity and greater loading capability for antibiotics elimination [5].…”
Section: Adsorption Methods (Ams)mentioning
confidence: 99%
“…Although various adsorbents have been applied for the uptake of pollutants ranging from biochar's, zeolites, clay, etc., the activated carbon has however been found to be an effective adsorbent for the uptake of inorganic and organic micropollutants [9]. Low-cost materials have also been extensively studied as alternative adsorbents for pharmaceuticals and recent studies have shown that banana stalk [10], corn cob and sugarcane bagasse [11], rice husk [12], argan tree nutshell [13], etc. could be used effectively as adsorbents.…”
Section: Introductionmentioning
confidence: 99%